Buddhist encounters and identities across East Asia - Heirman, Ann. (Dynamics in the History of Religions, 2018)
Encounters, networks, identities and diversity are at the core of the history of Buddhism. They are also the focus of Buddhist Encounters and Identities across East Asia , edited by Ann Heirman, Carmen Meinert and Christoph Anderl. While long-distance networks allowed Buddhist ideas to travel to all parts of East Asia, it was through local and trans-local networks and encounters, and a diversity of people and societies, that identities were made and negotiated. This book undertakes a detailed examination of discrete Buddhist identities rooted in unique cultural practices, beliefs and indigenous socio-political conditions. Moreover, it presents a fascinating picture of the intricacies of the regional and cross-regional networks that connected South and East Asia.